INTEGRATING AI WRITING ASSISTANTS INTO THE ESL CURRICULUM: OPPORTUNITIES AND CHALLENGES FOR TEACHERS - Muratova Khurshida Ne’matullo qizi, (TADQIQOTLAR, 2025)
Abstract The  rise  of  AI-powered  writing  assistants  like  Grammarly,  QuillBot,  and ChatGPT  is  transforming  the  landscape  of  English  as  a  Second  Language  (ESL) instruction. While students increasingly rely on these tools for writing tasks, teachers are often left navigating the opportunities and risks of integrating AI into classroom practice.  This  study  explores  ESL  teachers’  perceptions,  practices,  and  challenges when incorporating AI writing tools into the curriculum. Through a mixed-methods approach  involving  a  teacher  survey  and  follow-up  interviews,  the  study  identifies pedagogical benefits such as personalized feedback, learner autonomy, and classroom efficiency, alongside challenges including ethical concerns, student overreliance, and insufficient professional development. The article argues that thoughtful integration of AI tools, supported by clear institutional policies and teacher training, is essential for maximizing their benefits in ESL writing instruction. Practical recommendations and implications for future research are also provided.